(untitled) (REMUNOM, 2025)
This work presents Mathematical Modeling as an alternative approach to teaching mathematical content in high school, promoting student protagonism in the learning process. In addition to a brief historical contextualization, the study discusses strategies for applying modeling in the classroom, based on concepts from Mathematics Education. The literature review highlights modeling as an essential tool for connecting mathematical concepts to real-world phenomena. In this context, the theory of curve fitting was explored using the Least Squares method, addressing simple linear, polynomial, exponential, and logistic models, with the latter being developed through the Ford-Walford method. Finally, practical activities are proposed for students to apply curve fitting in the creation of mathematical models, encouraging hypothesis formulation and interaction with real and social problems.